Evaluation of the anthelmintic activity of Acacia cyanophylla Lindl against gastrointestinal nematodes of sheep: in vivo study - Akkari H.; Darghouth M.A.; Ben Salem H. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
The potential use of Acacia cyanophylla Lindl. (acacia), a tanniniferous shrub species, as a biologic way to reduce gastro-intestinal parasites was tested in grazing Barbarine lambs. Three groups of 10 lambs each were allocated to one of the following dietary treatment according to a cross-over design: grazing native pasture free of acacia and other woody species (grass group), grazing acacia (acacia group), and grazing acacia after daily oral administration of 40 g polyethylene glycol (PEG mol. weight 4000) (acacia plus PEG-group). PEG, a potent deactivating agent for condensed tannins, was mixed in water (1 kg in 2 l of water) and administered orally. Animals received daily at 8:30 h 300 g concentrate, and were then allowed to graze in the pasture or in the acacia plantation from 10:00 h to 16:00 h. Oaten hay (500 g) was distributed to lambs in the barn at 16:30 h. Each of the three experimental periods lasted 4 weeks. When lambs were on acacia diet they showed a significantly lower (P<0,05) mean faecal egg counts (FECs) than those on grass, 849.1 ± 453.6 epg and 1001.8 ± 511.8 epg, respectively. The addition of PEG to the acacia diet resulted in an increase in the daily weight gain and plasmatic uraemia concentrations to levels similar to that in the case of grass.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)